Ghana - Building Local Capacity for Integrated Coastal Zone Management - Mohan, P. C. (World Bank, Washington, DC, 2012)
During 1996 and 1997, a series of Bank-assisted workshops were held under the auspices of the Environmental Protection Agency, Ghana. They intended to: 1) raise awareness among coastal communities of the need for better management of the marine and coastal ecosystem; 2) identify the priority needs of coastal communities; 3) identify appropriate, cost-effective interventions for addressing these needs; 4) raise awareness of ongoing initiatives to support such interventions; and 5) assist coastal communities in the design of appropriate small-scale initiatives to address priority needs.